1996
DOI: 10.1007/s004649910028
|View full text |Cite
|
Sign up to set email alerts
|

Videothoracoscopy An effective method for evaluating and managing thoracic trauma patients

Abstract: Videothoracoscopy is a safe, accurate, minimally invasive, and potentially cost-effective method for the diagnosis and therapeutic management of thoracic trauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…Diagnostic and therapeutic indications in trauma have increased with the growing enthusiasm and training of trauma surgeons in endoscopic techniques. Overall, thoracoscopy is indicated in hemodynamically stable patients for the identification and control of continuous bleeding [12], from suspected mediastinal, cardiac [13,28] or diaphragmatic injuries [9,25], evacuation of retained posttraumatic hemothorax [14,10] and the treatment of post-traumatic bronchopleural fistulae [18] and diaphragmatic injuries.…”
mentioning
confidence: 99%
“…Diagnostic and therapeutic indications in trauma have increased with the growing enthusiasm and training of trauma surgeons in endoscopic techniques. Overall, thoracoscopy is indicated in hemodynamically stable patients for the identification and control of continuous bleeding [12], from suspected mediastinal, cardiac [13,28] or diaphragmatic injuries [9,25], evacuation of retained posttraumatic hemothorax [14,10] and the treatment of post-traumatic bronchopleural fistulae [18] and diaphragmatic injuries.…”
mentioning
confidence: 99%
“…An exhaustive review of the North American experience published in 1984 [14], that included a total of 4766 patients treated before the advent of VATS, showed that blood clots persisted in 4% of patients with a 10-day mean hospital stay. More recent reviews showed similar results [17] and have led to an unanimous consensus on the need to perform an accurate pleural cavity lavage. However, there are different views as to how this goal may be achieved, even among those who perform VATS with traditional instruments or a rigid video-thoracoscope [18].…”
Section: Discussionmentioning
confidence: 61%
“…Thoracoscopy has a role in both the diagnosis and treatment of trauma [5][6][7][8][9][10][11]. These indications are likely to expand with increased experience and improvements in instrumentation.…”
Section: Indications For Thoracoscopymentioning
confidence: 99%
“…These patients are at risk for diaphragmatic injury that can effectively be investigated by thoracoscopy, especially if concomitant intraabdominal injury is a remote possibility. Wong et al [9] documented that 9 of 10 (90%) diaphragmatic injuries were confirmed by thoracoscopy. Uribe et al [11] evaluated 28 patients with thoracoabdominal penetrating wounds and identified diaphragmatic injury in 9 (32%) of them.…”
Section: Diagnostic Indications: Diaphragmatic Injurymentioning
confidence: 99%
See 1 more Smart Citation